1971
DOI: 10.1037/h0030458
|View full text |Cite
|
Sign up to set email alerts
|

Hot and crowded: Influence of population density and temperature on interpersonal affective behavior.

Abstract: During exposure to conditions of high population density and high temperature, human interpersonal affective behavior as indicated by measures of liking or disliking another person was found to be more negative than during exposure to comfortable temperatures and low population density. Additional affective variables were also negatively influenced by temperature and density manipulations. The results parallel those in the animal literature reflecting deterioration of "social relations" under conditions of ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
147
3
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(165 citation statements)
references
References 12 publications
12
147
3
1
Order By: Relevance
“…As hypothesized, females who viewed a relatively unpleasant affect-evoking (serious) set of TV commercials gave more positive attraction responses than those who saw a relatively pleasant affect-evoking (humorous) set of commercials. These findings appear to contradict those reported in previous work (Griffitt, 1970;Griffitt & Veitch, 1971;Gouaux, 1971), which indicated higher attraction responses for pleasant induced affective states than for unpleasant states.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As hypothesized, females who viewed a relatively unpleasant affect-evoking (serious) set of TV commercials gave more positive attraction responses than those who saw a relatively pleasant affect-evoking (humorous) set of commercials. These findings appear to contradict those reported in previous work (Griffitt, 1970;Griffitt & Veitch, 1971;Gouaux, 1971), which indicated higher attraction responses for pleasant induced affective states than for unpleasant states.…”
Section: Discussioncontrasting
confidence: 99%
“…It follows from this proposition that any stimulus, such as attitude similarity, that influences attraction also can be shown to have affect-arousing properties (Byrne & Clore, 1970;Gormly, 1971). Several investigations (Griffitt, 1970: Griffitt & Veitch, 1971Gouaux, 1971) have provided strong support for this hypothesis by examining the effects of induced affect on evaluative responses. When affect is independently induced (by means of effective temperature, population density, or movie content) and proportion of attitudinal sirnilarity is also varied, attraction is found to be a joint function of the two sources of affect.…”
mentioning
confidence: 99%
“…The immediacy and salience of reduced space are intensified, for instance, through the operation of physical stress factors such as temperature and noise. Griffit and Veitch (1971) observed that interpersonal affective responses were significantly more negative under conditions of high temperature and high density than under those of comfortable temperature and low density. Also, it is plausible that noise, through its unwelcomed infringement on the individual's personal space, also serves to increase the salience of spatial restriction and thereby intensify the experience of crowding.…”
Section: Physical Variabzesmentioning
confidence: 93%
“…Such studies have generally been of two types, those which define crowding in terms of group size and those which manipulate it in terms of room size. The research of Rivlin (1970), Hutt andVaizey (1966), and Griffit and Veitch (1971) represent the first type of investigation, while those of Freedman (1970) and Freedman, Klevansky, and Ehrlich (1971) represent the second. Results from the first set of studies indicate that members of larger groups are more aggressive and asocial than those of smaller ones, regardless of whether the setting is a psychiatric ward, a playground, or a psychological experiment.…”
Section: Previous Research On Crowdingmentioning
confidence: 99%
“…49 Loud music may further impair communication between customers, preventing the de-escalation of fractious encounters. A range of other environmental factors can act as irritants such as poor air quality, 43 increased temperature [50][51][52] and uncomfortable furniture. 43,53 Moreover, dim lighting reduces the capacity for formal surveillance by premises guardians, impairs communication and increases the likelihood of collisions.…”
Section: Environmental Factorsmentioning
confidence: 99%